Fundamentals of Entrepreneurship (ENT300) : Al-Biruni Tuition Centre/ Jenickson Juan … [et al.] - Juan, Jenickson; Abdul Wahab, Noraishah; Merdicken, William Nichole; Jaafar, Farizah Syahirah; Wan Zainal Abidin, Sharifah Aishah (2018)
Al-Biruni Tuition Centre is our company name which provide teaching lesson and tutoring as our services. A tuition centre is maybe a common service that has been provided by any company but somehovy we will try our best to deliver the best services based on the syllabus that we have, the questions for our students and hope to help students to enhance their understanding in the syllabus so that they can score in their exams well with flying colours.